The Stepping Stones and Creating Futures intervention to prevent intimate partner violence and HIV-risk behaviours in Durban, South Africa: study protocol for a cluster randomized control trial, and baseline characteristics - Andrew Gibbs; Laura Washington; Samantha Willan; Nolwazi Ntini; Thobani Khumalo; Nompumelelo Mbatha; Yandisa Sikweyiya; Nwabisa Shai; Esnat Chirwa; Michael Strauss; Giulia Ferrari; Rachel Jewkes (BMC Public Health, 2017)
Abstract Background Preventing intimate partner violence (IPV) remains a global public health challenge. Studies suggest urban informal settlements have particularly high levels of IPV and HIV-prevalence and these settlements are rapidly growing. The current evidence base of effective approaches to preventing IPV recognizes the potential of combining economic strengthening and gender transformative interventions. However, few of these interventions have been done in urban informal settlements, and almost none have included men as direct recipients of these interventions. Methods Stepping Stones and Creating Futures intervention is a participatory gender transformative and livelihoods strengthening intervention. It is being evaluated through a cluster randomized control trial amongst young women and men (18–30) living in urban informal settlements in eThekwini Municipality, South Africa. The evaluation includes a qualitative process evaluation and cost-effectiveness analysis. A comparison of baseline characteristics of participants is also included. Discussion This is one of the first large trials to prevent IPV and HIV-vulnerability amongst young women and men in urban informal settlements. Given the mixed methods evaluation, the results of this trial have the ability to develop a stronger understanding of what works to prevent violence against women and the processes of change in interventions. Trial registration NCT03022370 . Registered 13 January 2017, retrospectively registered.